Area studies and the disciplines: Japanese Studies and anthropology in comparative perspective. Issue 2 (2nd July 2020) - Ben-Ari, Eyal
ABSTRACT: This article analyzes the social and institutional dynamics by which knowledge in Japanese studies is produced in the English-using academic world, the dominant global academic system, which as such is an arbiter for much of what "we" take as research. It utilizes the case of Japanese Studies as the analytical focus because it has been the site of great changes during the past seven or so decades, is rooted in a number of (linguistic) academic communities, and has been studied by the whole variety of the social scientific disciplines. This article tackles four issues. First, it sketches out the reasons for the continued interest in and development of Japanese Studies that differ from other area studies by tackling its adaptive potential (in institutional terms). Second, by situating Japanese Studies in terms of the global production of knowledge it defines how Japanese Studies is variously seen as peripheral, marginal or provincial in terms of the Euro-American centers. Third, given the ever-increasing theoretical citation in articles published in Japanese Studies (as in other regional studies) it analyses the division of labor between the disciplines and area studies. Fourth, it examines the importance of Japanese popular culture for its growth as an outcome of wider social processes within the academic dynamics of American and British universities. This article tackles these issues in an exploratory and purposely provocative manner.